The influence of enhanced vegetation index, proximity to national borders, proximity to protected areas, and proximity to water on malaria case prevalence in Sub-Saharan Africa, 2000-2020 - Dzokoto, Maxwell Kwame; Mensah, Benjamin Tetteh; Osei-Owusu, William; Adam, Ibrahim; Kwashie, Solomon D. Y. (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aimed to assess the effect of enhanced vegetation index, proximity to national borders, proximity to protected areas, and water on malaria morbidity in Sub-Saharan Africa. Methods: Data were pooled from the Demographic and Health Surveys (DHS) conducted in 32 Sub-Saharan African countries spanning 2000 to 2020. Women’s standard weights were denormalized and bivariate analyses were conducted to identify potential confounders. Two models were fitted; model 1 involved primary exposure variables and model 2 involved primary exposure variables adjusted for significant confounders. The final interpretation of the results was based on model 2. Results: The prevalence of malaria cases was 23.1%, The risk of children suffering malaria in households that belong to the 3rd quantile of the vegetation index is 27% less compared to children that belong to the households in the 1st quantile of the vegetation index [aOR=0.73, 95%CI: 0.55-0.99; p-value<0.05]. Children belonging to households in the 4th quantile of proximity to water have a 33% higher risk of suffering from malaria compared to households that are closer to water [aOR=1.33, 95%CI:1.08-1.63; p-value<0.01]. Conclusions: Environmental factors have been found to influence malaria morbidity among children in SSA. Intervention should be targeted at households especially those that are closer to water with more children under five to ensure full access and use of ITNs among all children under five as part of the overall goal of achieving the health-related SDGs.